Identification of new investment opportunities for East Midlands Early Growth Fund established by E-Synergy Ltd. - Markova, Ralitsa; Sajwan, Varun; Damania, Priti (2009)
This report looks at the economic growth of the East Midlands region and provides an overview of the venture capital activity with respect early stage investment in UK and specifically in the East Midlands region. Done under the management project guidelines set by the East Midlands Early Growth Fund (EMEGF), managed by E-Synergy Ltd, this report aims to recommend 5 early stage ventures to the investment committee of EMEGF. Further, it provides recommendations to venture capitalists on the various avenues, both traditional and non-traditional, that are available as part of the active process of searching for startups in order to increase their deal flow. Finally, this report opens further research possibilities in related fields of assessing the performance of current venture capital portfolio and also determining the success of a fund by other parameters such as comparing the deal flow of a venture capitalist fund to the successful exits done by the fund.